Chitosan Nanofibers for Specific Capture and Nondestructive Release of CTCs Assisted by pCBMA Brushes. Issue 36 (22nd July 2016) - Sun, Na; Liu, Min; Wang, Jine; Wang, Zhili; Li, Xinpan; Jiang, Bin; Pei, Renjun
Abstract : Over the last decade, significant progress has been made to develop sensitive devices for the capture of circulating tumor cells (CTCs) from blood of cancer patients. However, simple capture and counting of CTCs cannot provide effective information for understanding the biology of them. In this work, a functional biointerface is fabricated for specific capture and nondestructive release of CTCs from blood samples. A nanostrucure of porous network based on chitosan nanofibers is fabricated by electrospinning, to mimic the function of extracellular matrices, and then the poly(carboxybetaine methacrylate) (pCBMA) brushes integrating onto nanofiber interface provide the effect of interfacial properties to control nonspecific cell adhesion and the multivalent immobilization of aptamers to induce high efficient and specific CTC capture. Furthermore, a complementary sequence is used to efficiently hybridize with the aptamer to achieve nondestructive release of the captured target cells, assisted by the flexible space provided by pCBMA brushes. This work also shows how nanostructure and the interface molecules regulate the morphology of the captured CTCs, and reveals the importance of the controllable cell morphology on biointerface for an effective nondestructive release of the captured CTCs. Abstract : A chitosan nanofiber substrate grafted with pCBMA brushes is fabricated to provide a 3D interface of porous network and an antifouling flexible space for the immobilized aptamers confronting with cells. The cooperation of pCBMA brushes and DNA aptamers ensures sensitive capture from blood with a considerable purity, and intact release of target cells is realized using a complementary DNA sequence.